A new approach to quantifying physical demand in rugby union - Lacome, M.; Piscione, J.; Hager, J.-P.; Bourdin, M. (Journal of Sports Sciences, 2014)
The objective of the study was to describe an original approach to assessing individual workload during international rugby union competitions. The difference between positional groups and between the two halves was explored. Sixty-seven files from 30 French international rugby union players were assessed on a computerised player-tracking system (Amisco Pro®, Sport Universal Process, Nice, France) during five international games. Each player`s action was split up into exercise and recovery periods according to his individual velocity threshold. Exercise-to-recovery (E:R) period ratios and acceleration were calculated. Results indicated that about 65% of exercise periods lasted less than 4 s; half of the E:Rs were less than 1:4, and about one-third ranged between 1 and 1:4 and about 40% of exercise periods were classified as medium intensity. Most acceleration values were less than 3 m·s-2 and started from standing or walking activity. Back row players showed the highest mean acceleration values over the game (P < 0.05). No significant decrease in physical performance was seen between the first and second halves of the games except for back rows, who showed a significant decrease in mean acceleration (P < 0.05). The analysis of results emphasised the specific activity of back rows and tended to suggest that the players` combinations of action and recovery times were optimal for preventing large decrease in the physical performance.